Integrating Telemedicine in Pharmaceutical Care for Remote Patient Populations: A Systematic Review of 2030 Saudi Vision Goals - Nawaf Ayesh Khalid Almutairi; Mohammed Saleh Almarshed; Mohammed Salem Almutairi; Shaykhah Mohammed Hamad Alsunaid; Yasir Abdullah Ahmed Alghamdi; Bandar Muteb Almutairi; Abdulaziz Abdulkarim Alanazi; Fahad Mohammed Alghwainem (International Journal of Medical Toxicology and Legal Medicine, 2024)
Saudi Arabia's Vision 2030 represents a transformative plan to improve healthcare access and quality, particularly for remote patient populations. Telemedicine has emerged as a promising solution to bridge the geographical and socioeconomic barriers to pharmaceutical care. This systematic review aims to explore the potential of integrating telemedicine in pharmaceutical care for remote patient populations within the context of Saudi Arabia's Vision 2030 goals. A comprehensive literature search was conducted using relevant databases, and studies were selected based on pre-defined inclusion and exclusion criteria. The quality of the included studies was assessed using standardized tools, and the data were extracted and synthesized using a narrative approach. The findings highlight the benefits and challenges of telemedicine in enhancing medication management, patient education, and medication adherence for remote patient populations. The review also identifies the key enablers and barriers for the successful implementation of telemedicine in pharmaceutical care, such as technological infrastructure, regulatory frameworks, and healthcare provider acceptance. The study provides recommendations for policy, practice, and research to support the integration of telemedicine in pharmaceutical care for remote patient populations in Saudi Arabia, in alignment with the Vision 2030 goals of improving healthcare access, quality, and efficiency.